2006
DOI: 10.3347/kjp.2006.44.1.95
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of pediculosis and scabies in preschool nursery children of Afyon, Turkey

Abstract: Scabies and pediculosis are ubiquitous, contagious, and debilitating parasitic dermatoses. The tendency of high prevalence of pediculosis and scabies among school and preschool age children has prompted us to conduct a head louse and scabies prevalence survey among preschool nursery children in our district. A school-based, crosssectional study was performed, with 1,134 children chosen for evaluation. All cases were evaluated by physical examination and a detailed, structured questionnaire. The infestation was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
17
2
3

Year Published

2007
2007
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(28 citation statements)
references
References 8 publications
(6 reference statements)
6
17
2
3
Order By: Relevance
“…On the other hand, our figure (10.2%) is higher than the following; 0.8% and 5.1% among preschool nursery (46) and school (47) children in Turkey, 1.8% among school children in Iran, (10) 3.0% among school children in Poland, (15) 3.7% among primary school children in Nigeria (48) , 5.2% in Saudi Arabia (49) , 5.5% in Egypt (50) , 6.5% among primary school children in Ethiopia (6) , and 6.8% among primary school children in Sierra Leone. (51) At the same time, the overall prevalence of scabies among our studied school students was 3.4%.…”
Section: Discussioncontrasting
confidence: 80%
See 1 more Smart Citation
“…On the other hand, our figure (10.2%) is higher than the following; 0.8% and 5.1% among preschool nursery (46) and school (47) children in Turkey, 1.8% among school children in Iran, (10) 3.0% among school children in Poland, (15) 3.7% among primary school children in Nigeria (48) , 5.2% in Saudi Arabia (49) , 5.5% in Egypt (50) , 6.5% among primary school children in Ethiopia (6) , and 6.8% among primary school children in Sierra Leone. (51) At the same time, the overall prevalence of scabies among our studied school students was 3.4%.…”
Section: Discussioncontrasting
confidence: 80%
“…The prevalence of infestation with scabies was found to be 1.06% among school children in Ethiopia, (6) 1.8% among school children in Chile, (14) 2.37% among school children in Argentina (53) , 2.6% among students in Egypt 52, and 2.2% among primary school children in Turkey. (7) On one hand, Onlen et al (54) , and Ciftci et al (46) noticed prevalence of scabies was 0.48% and 0.4%, respectively among school and preschool nursery children in Turkey. On the other hand, our figure is less than that of El-Rifaie et al (20) ; they illustrated prevalence of infestation 5.8% among primary school children in Beni Suef Governorate, Egypt.…”
Section: (14)mentioning
confidence: 99%
“…Not a single case of head lice infestation was identified. The latter has been reported at a prevalence ranging from 0 to 28% 11,[16][17][18][19] in primary schools in various countries. In African study participants with similar hair to ours, the prevalence was 17AE1% in Kenya, 20 6AE8% in Sierra Leone, 21 and 3AE1% in urban and 0AE1% in rural Nigerian children.…”
Section: Discussionmentioning
confidence: 99%
“…Maternal education and occupation had an impact on the occurrence of scabies in children. A study in Turkey found that infestation was more common among children whose mothers were housewives than among educated and employed mothers [14]. In our study, the delay in diagnosis was related to the delay in consultation which was up to 120 days.…”
Section: Discussionmentioning
confidence: 41%